2016
DOI: 10.1093/gbe/evw180
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication and Gene Expression Changes Play a Role in the Evolution of Candidate Pollen Feeding Genes inHeliconiusButterflies

Abstract: Heliconius possess a unique ability among butterflies to feed on pollen. Pollen feeding significantly extends their lifespan, and is thought to have been important to the diversification of the genus. We used RNA sequencing to examine feeding-related gene expression in the mouthparts of four species of Heliconius and one nonpollen feeding species, Eueides isabella. We hypothesized that genes involved in morphology and protein metabolism might be upregulated in Heliconius because they have longer proboscides th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…emphasizing that these 70 cocoonase genes were found within moth and butterfly families, which indicates that the cocoonase is Lepidoptera-specific (Fig 1). In addition, multiple copies of cocoonase were identified in the butterflies, consistent with recent research on Heliconius butterflies, which uncovered the role of duplicated cocoonase genes in pollen feeding [37][38][39]. While, there was single copy in most moths except Plutella xylostella, Trichoplusia ni, Plodia The phylogenetic tree was constructed using the Maximum Likelihood method, based on the Poisson correction model with 1,000 bootstrap replicates, and bootstrap support values more than 50% were shown in the tree.…”
Section: Plos Geneticssupporting
confidence: 77%
“…emphasizing that these 70 cocoonase genes were found within moth and butterfly families, which indicates that the cocoonase is Lepidoptera-specific (Fig 1). In addition, multiple copies of cocoonase were identified in the butterflies, consistent with recent research on Heliconius butterflies, which uncovered the role of duplicated cocoonase genes in pollen feeding [37][38][39]. While, there was single copy in most moths except Plutella xylostella, Trichoplusia ni, Plodia The phylogenetic tree was constructed using the Maximum Likelihood method, based on the Poisson correction model with 1,000 bootstrap replicates, and bootstrap support values more than 50% were shown in the tree.…”
Section: Plos Geneticssupporting
confidence: 77%
“…De novo transcriptome assemblies for H. charithonia , H. sara , and H. doris were downloaded from Dryad with data identifier doi: 10.5061/dryad.ds21fv5 (Catalán et al 2018). Transcriptomes from H. erato and H. melpomene were downloaded from Dryad with data identifier doi: 10.5061/dryad.8d724 (Smith et al 2016). RNA-sequencing (RNA-seq) data for all the species were downloaded from ArrayExpress: E-MTAB-6810 (Catalán et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Like all butterflies, Heliconius lack cocoons, and it has been suggested that cocoonase homologues may have been coopted for use in digesting pollen proteins [62,63], potentially weakening the pollen wall. Cocoonase underwent several duplications along the lineage leading to Heliconius and their sister genus, Eueides, with an additional duplication specific to Heliconius and a further duplication in H. melpomene [63]. However, a functional role for cocoonase in pollen feeding has not yet been directly demonstrated.…”
Section: (C) Using Old Traits For New Purposesmentioning
confidence: 99%